The ANALYSIS OF THE DAMAGE LEVEL AND COST ESTIMATE MAINTENANCE OF FACULTY OF NURSING UNIVERSITY OF JEMBER - Helda Frista Oktavia; Hernu Suyoso; Nunung Nuring Hayati (Universitas Jember, 2020)
The Jember University Faculty of Nursing building is on the Tegal Boto campus of Jember University, which was built in 2008 for the Dekanat building and 2010 for the laboratory building so that it can be seen that the age of the Faculty of Nursing building has reached more than 10 years. Therefore it is necessary to evaluate and evaluate the condition of the building by analyzing the level of damage and calculating maintenance costs. This study uses the Analytical Hierarchy Process (AHP) method with the Expert Choice version 11 assistance program. The analysis process of the Dekanat’s building produced 16 elements that were slightly damaged and 8 other elements were in good condition. Whereas for the laboratory building there were 11 elements that suffered minor damage and 10 other elements had good conditions. The condition index value for the Dekanat building is 99.73% and the laboratory building is 98.49%, both of which are included in the Zone 1 Building Condition Index between 85% - 100% which has excellent conditions. The highest priority in maintenance and maintenance is in the exterior wall ceramic element components and the lowest priority is in the shutters component. So that the total cost required in the care and maintenance of the Dekanat building is Rp. 26,119,595.05 and for the laboratory building Rp. 48,513,395.38. Bangunan gedung Fakultas Keperawatan Universitas Jember berada di kampus Tegal Boto Universitas Jember yang dibangun pada tahun 2008 untuk gedung dekanat dan 2010 untuk gedung laboratorium, sehingga dapat diketahui bahwa umur bangunan gedung Fakultas Keperawatan telah mencapai 10 tahun lebih. Oleh karena itu diperlukan adanya evaluasi dan penilaian kondisi bangunan dengan menganalisa tingkat kerusakan dan menghitung biaya pemeliharaan. Penelitian ini menggunakan metode Analytical Hierarchy Process (AHP) dengan program bantu Expert Choice versi 11. Proses analisa terhadap gedung dekanat menghasilkan 16 elemen mengalami kerusakan ringan dan 8 elemen lainnya mempunyai kondisi baik. Sedangkan untuk gedung laboratorium terdapat 11 elemen mengalami kerusakan ringan dan 10 elemen lainnya mempunyai kondisi baik. Nilai indeks kondisi untuk gedung dekanat sebesar 99.73% dan untuk gedung laboratorium sebesar 98.49%, keduanya masuk dalam Indeks Kondisi Bangunan Zona 1 antara 85% - 100% yang mempunyai kondisi baik sekali. Prioritas tertinggi dalam pemeliharan dan perawatan terdapat pada komponen elemen keramik dinding eksterior dan prioritas terendah terdapat pada komponen daun jendela. Sehingga total biaya yang diperlukan dalam perawatan dan pemeliharaan untuk gedung dekanat sebesar Rp. 26,119,595.05 dan untuk gedung laboratorium sebesar Rp. 48,513,395.38.